Perencanaan Perawatan Preventif pada Blanking Dies untuk Mengurangi Biaya Operasinal - Andira Andira; Arich Gunawan Bayu Putra (President University, 2017)
PT. UK, an automotive producer, is one of the vendors of a motorcycle manufacturing company. During the production, it is needed Dies, jig and inspection jig. Dies is used for supporting the cutting and formingsheet metal into steel pipe for making a certain product. During the process, blanking Dies component is getting many collisions and frictions that can cause machine breakdowns. These breakdowns have an impact to production loss time. In 2016, the production was 697.41 hours. Not only the production loss, the customer deliveries were also late that caused penalty costs from customers. Therefore, the preventive maintenance is very important for the machine running during the production process especially for blanking Dies. By using FMEA, there are three critical components of three blanking Dies types. The calculation and simulation of decreasing shows that the number of breakdown can be decreased by 33,84% and the maintenance cost canbe saved by 26,22% compare to the current system.